The Effect Of CFO Demographics On Fraudulent Financial Reporting - Yulia Frischanita; Yustrida Bernawati (Jurnal Akuntansi, 2020)
This study aims to examine the effect of CFO demographics on financial statement fraud. The results contribute to companies for increasing CEO and CFO elections and corporate governance designed to prevent illegal actions. The sample in this study was manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 with 308 data and hypothesis testing using multiple regression analysis techniques. The test results show that the age of the CFO affects the fraudulent financial statements. More mature the CFO engage with fraudulent financial statements. Other results indicate that the level of education, gender and experience of the CFO have no effect on financial statement fraud. The control variable used is ROA which has a positive effect on financial statement fraud. While company size and leverage have a negative effect on financial statement fraud.